Prevalence and Increase over Time of Twelve Self-reported Skin Symptoms: Data from Two Representative Samples from 1998 and 2015 - Hanna Reich; Elmar Brähler; Uwe Gieler; Jörg Kupfer (Medical Journals Sweden, 2022)
Point prevalence estimates for common skin symptoms vary widely. Most research has focussed on a few symptoms and a single point of observation. The aim of this study is to determine point prevalence rates for 12 self-reported skin symptoms in 1998 and 2015 and to assess changes in the reporting of skin symptoms over time. Symptoms were assessed by 2 national face-to-face household surveys of representative samples of the German general population (n1998=2,079, n2015=2,511). Point prevalence ranges were 6.8-26.2% in 1998 and 11.6-32.1% in 2015. Dandruff, body odour, pimples, and an itchy scalp were the 4 most common skin symptoms, each of which affected more than 20% of the population at both time-points. For almost all symptoms, a statistically significant increase, with very small to small effect sizes, was observed over time. The increase in skin symptoms over time is congruent with the increase in skin diseases reported by the Global Burden of Disease study.